On attainability of Hashin-Shtrikman bounds by iterative hexagonal layering. Plane elasticity problems - Lewiński, T.; Othman, A.M. (Archives of Mechanics, 1997)
The paper presents a derivation of the Hashin—Shtrikman bounds for the plane elasticity problems and for the Kirchhoff problem of plates in bending. A two-dimensional counterpart of the method of FRANCFORT—MURAT [1] is applied. The method consists of three subsequent layerings along the directions of vertices of a unilateral triangle.